2017
DOI: 10.1128/jvi.00904-17
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Effects of the Glucocorticoid Receptor and Krüppel-Like Transcription Factor 15 on Bovine Herpesvirus 1 Transcription and Productive Infection

Abstract: Bovine herpesvirus 1 (BoHV-1), an important bovine pathogen, establishes lifelong latency in sensory neurons. Latently infected calves consistently reactivate from latency following a single intravenous injection of the synthetic corticosteroid dexamethasone. The immediate early transcription unit 1 (IEtu1) promoter, which drives bovine ICP0 (bICP0) and bICP4 expression, is stimulated by dexamethasone because it contains two glucocorticoid receptor (GR) response elements (GREs). Several Krüppel-like transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(86 citation statements)
references
References 89 publications
(145 reference statements)
7
72
0
Order By: Relevance
“…2A). We also examined KLF family members that are induced during BoHV-1 reactivation from latency (11) because certain KLF family members cooperate with the GR to stimulate the BoHV-1 immediate early transcription unit 1 (IEtu1) promoter (12). The FL ICP0 construct was cotransfected into Neuro-2A or Vero cells with the GR, a KLF family member, and a Renilla luciferase gene driven by a minimal thymidine kinase (TK) promoter.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2A). We also examined KLF family members that are induced during BoHV-1 reactivation from latency (11) because certain KLF family members cooperate with the GR to stimulate the BoHV-1 immediate early transcription unit 1 (IEtu1) promoter (12). The FL ICP0 construct was cotransfected into Neuro-2A or Vero cells with the GR, a KLF family member, and a Renilla luciferase gene driven by a minimal thymidine kinase (TK) promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that DEX treatment induced KLF15 expression in many TG neurons (11,12), suggesting that this is part of the general stress response. KLF15, like other KLF family members, resembles the Sp1 transcription factor family, and both families interact with GC-rich motifs (17,34,35).…”
Section: Figmentioning
confidence: 91%
See 3 more Smart Citations